11.1k views
1 vote
What is the simplified form of this expression?

(-x2 + x) + (4x2 − x − 1)

What is the simplified form of this expression? (-x2 + x) + (4x2 − x − 1)-example-1
User Enkor
by
4.1k points

1 Answer

8 votes

Answer: Choice A is correct

Step-by-step explanation:

The x^2 terms add to -x^2+4x^2 = 3x^2

The x terms add to x+(-x) = x-x = 0x = 0

The constant -1 doesn't have anything to pair with it, so it just stays as is.

So overall we end up with 3x^2-1

User Lytenyn
by
5.9k points